Surface-Rearranged Pd3Au/C Nanocatalysts by Using CO-Induced Segregation for Formic Acid Oxidation Reactions - Lee, Sang-Young; Jung, Namgee; Cho, Jinwon; Park, Hee-Young; Ryu, Jaeyune; Jang, Injoon; Kim, Hyoung-Juhn; Cho, EunAe; Park, Yeung-Ho; Ham, Hyung Chul; Jang, Jong Hyun; Yoo, Sung Jong (AMER CHEMICAL SOC, 2014)
Carbon-supported Pd3Au nanoparticle catalysts were synthesized via chemical reduction. Surface segregation of Pd in Pd3Au catalyst was achieved via heat treatment under air, Ar, CO-Ar, and CO atmospheres, in order to obtain a surface with changed structures and composition. The surface composition was analyzed by electrochemical methods, and the Pd surface composition was observed to increase from 67.2% (air (asp) sample) to 80.6% (CO sample) after heat treatment under a CO atmosphere. The CO-induced surface segregation of the Pd3Au electrocatalyst resulted in a significantly improved formic acid oxidation (from 6.93 to 18.11 mA cm(-2)) and stability (from 0.66 to 2.01 mA cm(-2)) compared to the sample prepared in air, as well as increased mass activity (from 199.20 to 520.55 A g(-1)), electrochemical surface area (ESA(Pd)) (from 61.08 to 95.68 m(2) g(Pd)(-1)), and specific activity (from 0.33 to 0.55 mA cm(Pd)(-1)), respectively. The electrochemical activities were significantly increased because of changes in the structure and composition of the surface due to the increased surface ratio of Pd promoted by CO heat treatment. The exchange of Pd and Au atoms between the surface and the bulk material was observed to influence formic acid oxidation and stable performance. The CO-induced surface segregation has the potential to greatly enhance the electrochemical activities and surface control of Pd-Au alloy nanoparticle with lower Pd contents.
Keywords: SINGLE-CRYSTAL ELECTRODES; METHANOL SYNTHESIS; PD; ELECTROOXIDATION; CATALYST; PALLADIUM; PLATINUM; NANOPARTICLES; GOLD; DECOMPOSITION